SISTEM INFORMASI PRODUK UNGGULAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KABUPATEN KETAPANG BERBASIS WEB - Novi Indah Pradasari; Eka Wahyudi; Darmanto Darmanto (Elkom : Jurnal Elektronika dan Komputer, 2021)
At the present time of the pandemic, it is difficult for the world's most unusual cuttlefish to market its products. Thus, umkm needs to be provided with facilities to market the products online. Special-based backends are one of the media for selling by-products on the catapult. The purpose of this research is to construct typical web-based appendage by-by-products. The purpose of this research is to construct typical web-based appendage by-by-products. Research methods used in the construction of systems on this research are the methods of research and development (R & D). This study provides several design systems, the design of system architecture, the DFD system, the design of the interface, and the design of system testing. The system was created using the framework laravel. As for the results of the final assignment research "typical web-based appendage". In this system, there are two users, the user as the store and the user as the buyer. On the user as a store there are several features that include input from store products, editing from products, confirmation of deliveries, responding to comments given by the buyer on the product, viewing the order data done by the buyer, and editing the store's data. While the user's features as the purchaser look at the product's data, see the store's data as a souvenir, order a by-product payment, confirm the order has been accepted, give an assessment of the product's already received, and edit the customer's data. The system was tested by using black box methods testing to see the effectiveness of a system built with test variables was 100%.